Membangun Theatre of Mind Program Variety Radio â€œSantai Sejenakâ€ Episode â€œMemoriesâ€ - Harista, Bekti Hanif; Oktora, Dina Dwika (Jurnal Ilmiah Multimedia dan Komunikasi, 2023)
Creating a theater of mind for every listener is important, because radio is an auditory mass media. The process of forming a theater of mind for each person is different depending on how people imagine what they hear. The author uses sound elements in the form of voice, music and sound effects that are often played and heard in the past in forming a theater of mind for listeners on the Santai Sejenak radio variety program episode "Memories". The goal is to build a nostalgic feeling for the listeners. The response of listeners who then sent stories about their memories during the event was a form of success in building this nostalgia. This was done by combining several existing elements. Among them are music, words and sound effects. When listeners can feel nostalgic, it means that the director's task in forming a theater of mind has been successful. One way to prove it is that there is a response from the listeners who send the story.